Transient increase in atherosclerotic plaque macrophage content following Streptococcus pneumoniae pneumonia in ApoE-deficient mice - Bazaz, Rohit; Marriott, Helen M.; Wright, Carl; Chamberlain, Janet; West, Laura E.; Gelsthorpe, Catherine; Heath, Paul R.; Maleki-Dizaji, Afsaneh; Francis, Sheila E.; Dockrell, David H. (Frontiers in Cellular and Infection Microbiology, 2023)
Despite epidemiological associations between community acquired pneumonia (CAP) and myocardial infarction, mechanisms that modify cardiovascular disease during CAP are not well defined. In particular, largely due to a lack of relevant experimental models, the effect of pneumonia on atherosclerotic plaques is unclear. We describe the development of a murine model of the commonest cause of CAP, Streptococcus pneumoniae pneumonia, on a background of established atherosclerosis. We go on to use our model to investigate the effects of pneumococcal pneumonia on atherosclerosis. C57BL/6J and ApoE-/- mice were fed a high fat diet to promote atherosclerotic plaque formation. Mice were then infected with a range of S. pneumoniae serotypes (1, 4 or 14) with the aim of establishing a model to study atherosclerotic plaque evolution after pneumonia and bacteraemia. Laser capture microdissection of plaque macrophages enabled transcriptomic analysis. Intratracheal instillation of S. pneumoniae in mice fed a cholate containing diet resulted in low survival rates following infection, confirming increased susceptibility to severe infection. Optimization steps resulted in a final model of male ApoE-/- mice fed a Western diet then infected by intranasal instillation of serotype 4 (TIGR4) S. pneumoniae followed by antibiotic administration. This protocol resulted in high rates of bacteremia (88.9%) and survival (88.5%). Pneumonia resulted in increased aortic sinus plaque macrophage content 2 weeks post pneumonia but not at 8 weeks, and no difference in plaque burden or other plaque vulnerability markers were found at either time point. Microarray and qPCR analysis of plaque macrophages identified downregulation of two E3 ubiquitin ligases, Huwe1 and Itch, following pneumonia. Treatment with atorvastatin failed to alter plaque macrophage content or other plaque features. Without antibiotics, ApoE-/- mice fed a high fat diet were highly susceptible to mortality following S. pneumoniae infection. The major infection associated change in plaque morphology was an early increase in plaque macrophages. Our results also hint at a role for the ubiquitin proteasome system in the response to pneumococcal infection in the plaque microenvironment.